Analysis of Company Value on Companies That Implement Enterprise Resource Planning (ERP) System (Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange) - Fendra, Fendra (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
This research aims to obtain differences in company value both pre-implementation & post-implementation of ERP system on period of 2009-2013 in manufacturing companies on the IDX. This conducted with One Group Pretest-Posttest Design, using secondary data. Based on purposive sampling criteria, consisted 16 companies. The method used is non-parametric, that is Wilcoxon Signed Ranks Test by SPSS 24 program. The result shows there is no significant increase by Tobin’s Q on post-implementation period. However, when divided into Industry Sector, there is no significant increase on Basic Industry & Chemicals and Miscellaneous Industry, and there is significant increase on Consumer Goods Industry. In brief, ERP system implementation have not able to improve the company value on post-implementation period within the fourth year to the sixth year.Keywords: Enterprise Resource Planning, System Implementation, Company Value, Tobin’s Q.REFERENCESAgeng, I., Noorlailie, S., & Isnalita. (2018). ERP Implementation Effect on Internal Control of Corporate Banking In Indonesia Stock Exchange Listing In 2014-2016. RJOAS.Anderson, M., Banker, N., & Menon, N. (2011). Implementing Enterprise Resource Planning Systems: Organizational Performance and the Duration of the Implementation. Journal of Information Technology Management, 197-212.Anggraini, L. E. (2014). Analisis Dampak Pengimplementasian Sistem Enterprise Resource Planning Terhadap Kinerja Perusahaan (Studi Kasus Pada Perusahaan Pengguna Sistem ERP yang Terdaftar di BEI periode 2004-2010).Ani, Y. N., & Yunita, I. (2015). Analisis Perbandingan Kinerja Keuangan Sebelum dan Setelah Penerapan ERP pada BCA,Tbk dan BNI,Tbk Periode Tahun 2001-2009. e-Proceeding of Management.Barney, J. (1986). Organizational Culture: Can It Be a Source of Sustained Competitive Adventage. Academy of Management Review, 656-665.Barney, J. (1991). Firm Resource and Sustained Competitive Adventage. Journal of Management, 99-120.Barton, P. (2001). Enterprise Resource Planning Factors Affecting Succes and Failure.Basoglu, N., Daim, T., & Kerimoglu, O. (2007). Organizational adoption of enterprise resource planning systems: A conceptual framework. Journal of High Technology Management Research, 73-97.Candra, S. (2012). ERP Implementation Success and Knowledge Capability. Procedia - Social and Behavioral Sciences 65 (ICIBSoS), 141-49.Chung, K. H., & Pruitt, S. W. (1994). A Simple Approximation of Tobin's Q. Financial Management, 70-74.Cooper, D. R., & Schindler, P. S. (2014). Business Research Methods, Twelfth Edition. New York: McGraw-Hill Irwin.Creswell, J. W. (2014). Research Design: Qualitative, Quantitative, and Mixed Methods Approaches 4th ed. California: SAGE Publications, Inc.Davenport, T. H. (1998). Putting the Enterprise Into the Enterprise System. Harvard Business Review.Fiakas, D. (2005). Tobin's q: Valuing Small Capitalization Companies. Crystal Equity Research.Galy, E., & Sauceda, M. J. (2014). Post-Implementation Practices of ERP Systems and Their Relationship to Financial Performance. Information and Management 51.Hall, J. A. (2011). Information Technology Auditing and Assurance Third Edition. South-Western, Cengage Learning.Hayes, A. (2019, April 15). Investopedia. Retrieved from Investopedia Web Site: https://www.investopedia.com/terms/q/qratio.aspHuang, Z., & Palvia, P. (2001). ERP Implementation Issues in Advance and Developing Countries. Business Process Management Journal, 276-284.Hunton, J. E., Lippincott, B., & Reck, J. L. (2003). Enterprise Resource Planning Systems: Comparing Firm Performance of Adopters and Nonadapters. International Journal of Accounting, 165-184.Hwang, W. (2011, June). The Drivers of ERP Implementation and Its Impact on Organizational Capabilities and Performance and Customer Value. The University of Toledo.Ince, H., Imamoglu, S. Z., Keskin, H., Akgun, A., & Efe, M. N. (2013). The Impact of ERP Systems and Supply Chain Management Practices on Firm Performance: Case of Turkish Companies. Procedia - Social and Behavioral Sciences, 1124-1133.Khawarizmi, M. (2018). Analisis Perbandingan Kinerja Keuangan Sebelum dan Sesudah Implementasi ERP (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI. Yogyakarta: Universitas Islam Indonesia.Kristianti, C. E., & Achjari, D. (2017). Penerapan Sistem ERP: Dampak Terhadap Kinerja Keuangan Perusahaan. Jurnal Akuntansi & Auditing Indonesia.Kurniawati, M., Gunarta, I. K., & Baihaqi, I. (2015). Dampak Implementasi Enterprise Resource Planning (ERP) Pada Kinerja Keuangan: Pendekatan Resources Based View. Jurnal Manajemen Teknologi, 1-9.Lindenberg, E. B., & Ross, S. A. (1981). Tobin's Q Ratio and Industrial Organization. The Journal of Business, 1-32.Marpaung, M. T. (2015). Analisis Kinerja Finansial Perusahaan Yang Mengimplementasi Sistem ERP (Studi Empiris Pada Perusahaan Listing di BEI Tahun 2002-2010. Yogyakarta: Universitas Sanata Dharma.Monk, E., & Bret, W. (2001). Concepts in Enterprise Resource Planning. Angewandte Chemie International Edition 4th Edition.Nicolaou, A. I., & Bajor, L. H. (2011). ERP System Implementation and Firm Performance. The Review of Business Information System.Nurhanifah, M. (2013). Analisis Kinerja Keuangan Perusahaan Sebelum Dan Sesudah Implementasi ERP Pada Perusahaan-Perusahaan Yang Terdaftar Di Bursa Efek Indonesia. Yogyakarta: Fakultas Ekonomi UII.Pracita, S. A., Isnalita, & Soewarno, N. (2018). Analisis Pengaruh Implementasi ERP Terhadap Profitabilitas dan Nilai Perusahaan. Jurnal Akuntansi Universitas Jember.Putri, & Putri, A. J. (2016). Analisis Perbandingan Kinerja Keuangan Sebelum Dan Setelah Implementasi Sistem ERP Pada Bank Yang Terdaftar Di Bursa Efek Indonesia (BEI). Yogyakarta: Fakultas Ekonomi UII.Rektiani, A., Rahayu, S., & Yudowati, S. P. (2017). Kinerja Keuangan dan Kapabilitas Perusahaan Sebelum dan Sesudah Implementasi Enterprise Resource Planning (ERP) (Studi Pada Perusahaan Manufakur Pengguna Enterprise Resource Planning Yang Terdaftar Di BEI Tahun 2008-2016). e-Proceeding of Management.Rini, W. F., & Febriani, D. (2017). Dampak Implementasi Enterprise Resources Planning (ERP) Atas Pengaruh Profitabilitas Terhadap Nilai Perusahaan. Jurnal Aset (Akuntansi Riset).Romney, M. B., & Steinbart, P. J. (2014). Accounting Information System 13th ed. Boston: Pearson.Ruivo, P. (2015). Using Resource Based View Theory to Asses the VAlue of ERP Commercial Packages in SMEs. Computer in Industry Journal, 105-116.Sekaran, U., & Bougie, R. (2016). Research Methods for Business: A Skill-Building Approach - Seventh Edition. Chichester, West Sussex, United Kingdom: John Wiley & Sons Ltd.Sofiana, D. N. (2017). Analisis Kinerja Kuangan Perusahaan Sebelum dan Sesudah Pengimplementasian Sistem ERP pada Sektor Manufaktur (Pada Perusahaan yang terdaftar di BEI). Semarang: Universitas Katolik Soegijapranata.Tarigan, Z. J. (2009). Pengaruh Implementasi ERP Terhadap Product Differentiation & Cost Leadership Dalam Meningkatkan Kinerja Perusahaan (Studi Kasus Manufaktur Jawa Timur). Jurnal Manajemen Pemasaran, 11-15.Voulgaris, F., Lemonakis, C., & Papoutsakis, M. (2015). The Impact of ERP Systems on Firm Performance: the Case of Greek Enterprise. Global Business and Economics Review.Wade, M., & Hulland, J. (2004). The Resource Based View and Information Systems Research, review, extension, and suggestion for future research. Management Information System, 107-142.Wolfe, J., & Sauaia, A. C. (2003). The Tobin's Q as a Company Performance Indicator, Developments in Business Simulation and Experiential Learning, Volume 30.